2012
DOI: 10.1016/j.physe.2011.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of graphene-based NEMS

Abstract: The possibility of designing nanoelectromechanical systems (NEMS) based on relative motion or vibrations of graphene layers is analyzed. Ab initio and empirical calculations of the potential relief of interlayer interaction energy in bilayer graphene are performed. A new potential based on the density functional theory calculations with the dispersion correction is developed to reliably reproduce the potential relief of interlayer interaction energy in bilayer graphene.Telescopic oscillations and small relativ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
61
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 55 publications
0
61
1
Order By: Relevance
“…Graphene sheets, the two-dimensional carbon nanostructure, amazingly exhibit the electrical, mechanical, thermal and optical properties (Jomehzadeh et al, 2015) that have been considered as a promising material for a wide range of applications (Lebedeva et al, 2012) such as composites, chemical sensors, ultra capacitors, transparent electrodes, photovoltaic cells, bio-devices (Zandiatashbar et al, 2014) and the gigahertz oscillator suggested based on the telescopic oscillation of graphene layers (Lebedeva et al, 2012). It is of great importance to simulate mechanical behavior of single/muti-layered graphene sheets accurately due to this wide scope of applications.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene sheets, the two-dimensional carbon nanostructure, amazingly exhibit the electrical, mechanical, thermal and optical properties (Jomehzadeh et al, 2015) that have been considered as a promising material for a wide range of applications (Lebedeva et al, 2012) such as composites, chemical sensors, ultra capacitors, transparent electrodes, photovoltaic cells, bio-devices (Zandiatashbar et al, 2014) and the gigahertz oscillator suggested based on the telescopic oscillation of graphene layers (Lebedeva et al, 2012). It is of great importance to simulate mechanical behavior of single/muti-layered graphene sheets accurately due to this wide scope of applications.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, graphene oscillators based on the interlayer sliding of graphene nanoribbons (GNRs) or graphene nanoflakes (GNFs) have been addressed [20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Fast mechanical response of such devices can be predicted from low Q-factor values obtained for relative vibrations [28,29] and self-retracting motion of graphene layers [29,30] observed experimentally [31]. Schemes and operational principles of a set of NEMS based on relative motion and interaction of graphene layers have been considered [7,[11][12][13]29,[32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Fast mechanical response of such devices can be predicted from low Q-factor values obtained for relative vibrations [28,29] and self-retracting motion of graphene layers [29,30] observed experimentally [31]. Schemes and operational principles of a set of NEMS based on relative motion and interaction of graphene layers have been considered [7,[11][12][13]29,[32][33][34][35]. It is worth mentioning a nanorelay [29] and inertial sensor [32] based on telescopic motion of graphene layers [29], memory cells based on motion of a graphene flake on a graphene layer [33,34], nanoelectromechanical switches based on changes of the distance between graphene layers [35] and in-plane relative displacement of layers [11], various nanosensors based on measurements of conductance changes at the in-plane relative displacement of layers of bilayer graphene [7,[11][12][13]35].…”
Section: Introductionmentioning
confidence: 99%